A formação universitária na construção da prática tradutória sob a ótica dos alunos - Ferreira, Andréa de Oliveira Gaspar (2014)
The purpose of this work is to comprehend the influence of university education in the construction of the translation practice of students in the last year of a specific Translation and Interpretation course of a community university at Baixada Santista, São Paulo/SP. It is assumed that a university course influences the practice construction of these students, who during the education get to know the steps that all translators go through or should go through, daily. The theoretical approach is based on translation studies and practice of translation as Arrojo (1993; 2002) Aubert (1989; 1990); Bordenave (1989); Barbosa (1990); Barbosa e Neiva (1997); Darin (1997); Brezolin (2000; 2003); Alves, Magalhães, Pagano (2011). The field research is developed in two parts, and has different methodological procedures. In the first part was performed an analysis of the Course Pedagogic Project, in the second, one it were applied two questionnaires to eighteen students: the first with opened and closed questions about the university education, translation practice, its challenge and steps. According to the Content Analysis (BARDIN, 1979), two analysis dimensions were determined: the first one ¿ translators¿ university education ¿ has highlighted aspects related to university education; and the second allowed the identification of different aspects concerning the translation practice. The study conducted to the following results: first related to the university education: there is a formative necessity related to translation and translation practice, so the students could be more aware of their role and task. Even though, the students are native speakers, and literate in Portuguese language we could infer that there is a lack of domain over this language and about the second analysis dimension, the translation practice, the results indicate a lack of initiative on behalf of the students to do research in reference materials. They have difficulty in expressing their arguments related to the difficulties encountered during the practice of translation that justify their solutions.